An overview on recent progress in photocatalytic air purification: Metal-based and metal-free photocatalysis - Sharma, Sarika; Kumar, Rohit; Raizada, Pankaj; Ahamad, Tansir; Alshehri, Saad M.; Nguyen, Van-Huy; Thakur, Sourbh; Nguyen, Chinh Chien; Kim, Soo Young; Le, Quyet Van; Singh, Pardeep (Environmental research, 2022)
Air pollution is becoming a distinctly growing concern and the most pressing universal problem as a result of increased energy consumption, with the multiplication of the human population and industrial enterprises, resulting in the generation of hazardous pollutants. Among these, carbon monoxide, nitrogen oxides, Volatile organic compounds, Semi volatile organic compounds, and other inorganic gases not only have an adverse impact on human health both outdoors and indoors, but have also substantially altered the global climate, resulting in several calamities around the world. Thus, the purification of air is a crucial matter to deal with. Photocatalytic oxidation is one of the most recent and promising technologies, and it has been the subject of numerous studies over the past two decades. Hence, the photocatalyst is the most reassuring aspirant due to its adequate bandgap and exquisite stability. The process of photocatalysis has provided many benefits to the atmosphere by removing pollutants. In this review, our work focuses on four main themes. Firstly, we briefly elaborated on the general mechanism of air pollutant degradation, followed by an overview of the typical TiO2 photocatalyst, which is the most researched photocatalyst for photocatalytic destruction of gaseous VOCs. The influence of operating parameters influencing the process of photocatalytic oxidation (such as mass transfer, light source and intensity, pollutant concentration, and relative humidity) was then summarized. Afterwards, the progress and drawbacks of some typical photoreactors (including monolithic reactors, microreactors, optical fiber reactors, and packed bed reactors) were described and differentiated. Lastly, the most noteworthy coverage is dedicated to different types of modification strategies aimed at ameliorating the performance of photocatalysts for degradation of air pollutants, which were proposed and addressed. In addition, the review winds up with a brief deliberation for more exploration into air purification photocatalysis. [Display omitted] •Recent progress in photocatalysis for air purification is reviewed.•Mechanism for degradation of air pollutants over photocatalysts is explained.•Photoreactors for the photocatalytic degradation of air pollutants are summarized.•Progress and drawback on the designs of photoreactors are provided.•Strategies for development of photocatalytic air purification are recommended.